O fantasma da palavra: a poética da ausência em A menina morta, de Cornélio Penna - Moreira, Douglas Carlos de Paula (2016)
This work intends to study the voids, the gaps and the textual absences in the novel A menina morta [The dead girl] (1954), written by Cornélio Penna. In this novel, we have found a structured narrative around the absence (starting with the absence of the very girl who gives title to the work), inviting the reader to look endlessly for an empty place that, paradoxically, leaves its mark in emotional repression form and social malaise. The reader look wants to see more, however is the least that the author offers, inscribing his fiction under the sign of negativity and emptying. We affirm that, in this novel, unlike his initial works, Cornélio Penna overcomes the fantastic strand, moving the transcendent area "ghosts" for the inexorable encounter with real.We have sought the theoretical foundation of this thesis in the literary theory, philosophy and psychoanalysis speeches, through the dialogue with the works of Sigmund Freud, Jacques Lacan, Maurice Blanchot, Giorgio Agamben, Walter Benjamin and Georges Didi-Huberman. Through these thinkers, we have tried to show the dialectic game which Cornélio Penna articulates among subjectivity and objectivity, through which the reality is implicated in the subjectivation modes. In A menina morta, therefore, the reality of patriarchy and slavery becomes more frightening than ghosts that inhabit the popular imagination. The territory chosen by Cornélio Penna to describe his historical drama makes from the myth the labyrinth of history, up against the events are stoned in a stagnant zone in which almost nothing happens, protruding the mourning and the melancholy. The characters connection is marked by the lack of communication, due to fear of saying and the resentment of shut up. So, to the characters remain the refuge of unsaid (up against the bans strength) and the dramatization of words and gestures. The ghost of the word is not – as you might guess – the silence; the ghost of the word is the lack of the name, is this nonspecific place where the thinking does not reach and the reason seems to fall apart. In short, it is about an opening to an inaccessible place, a tragic aporia, formed by a time of expecting and a place of passage.